Sodium azulene sulfonate reverses multidrug resistance in K562/A02 cells - Wang, Ziwei; Zhou, Na; Zhao, Jianqi; Zhang, Xin (Cellular and Molecular Biology, 2019)
Overexpression of p-glycoprotein (p-gp) is the main cause of multidrug resistance and chemotherapy failure in leukemia. Sodium azulene sulfonate (SAS) was used to reverse the multidrug resistance of human leukemia adriamycin-resistant strain K562/A02, and the underlying mechanism was investigated. Human leukemia cell line K562 and drug-resistant cell line K562/A02 in logarithmic phase were used in this study. After 48 hours of treatment of K562/A02 cells with SAS, the intrinsic cytotoxicity of chlorogenic acid and its sensitivity to adriamycin (ADM) were determined with MTT assay. The degree of reversal was calculated. Using ADM accumulation and rhodamine 123 efflux experiments, the average fluorescence intensity of ADM and rhodamine 123 (Rh123) in chlorogenic acid-treated K562/A02 cells was determined flow cytometrically. The expressions of p-gp, t-Akt and p-Akt in K562/A02 cells were assayed using Western blotting. SAS had almost no cytotoxic effect, and the degree of inhibition was only about 20% at the highest concentration of 100 mu-M. The EC50 of MDR reversal by SAS was in the nano range (539±37nM), and it had a high selectivity index for normal cells (>185). The accumulation of ADM in drug-resistant cells was increased significantly after treatment with 1 and 5 mu-M SAS, while the efflux of Rh123 was significantly inhibited, suggesting that SAS reversed MDR by inhibiting p-gp function. Western blotting experiments showed that SAS downregulated the expression of p-gp by inhibiting PI3K/Akt signaling pathway. This contributed to the reversal of drug resistance.SAS effectively reverses multidrug resistance in vitro by inhibiting the function of p-gp in K562/A02 cells, through a mechanism involving downregulation of the P13K/Akt signaling pathway. Therefore, SAS may be a potential candidate drug for reversal of MDR.